Pendampingan Budaya Perilaku Hidup Bersih dan Sehat Pada Anak Desa Kapas Nganjuk Untuk Mewujudkan Sekolah Sehat - Fiyya Faiz Aufa; Siti Kalimah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
The PHBS program is a health promotion effort that aims to make Indonesians live in a clean and healthy environment. PHBS program in the community environment is the main thing that must be considered because it plays an important role in the spread of diseases both infectious and not, both in urban and rural areas. In particular, this PHBS program helps teachers and students in rural children to learn lifestyles that are in accordance with their portions. This research is aimed at informing and empowering PHBS in this school. The results of the study showed that in cotton village children Nganjuk clean and healthy living behavior is still not well conditioned, therefore the PHBS program is intended to realize the highest degree of public health as a gift for the development of productive human resources. While public awareness of health and PHBS, especially in the children of Kapas Nganjuk village, is still average. For this reason, phbs extension is expected to be an effort to realize all the importance of empowering PHBS in everyday life while providing knowledge how to realize it so that it can realize healthy schools.